2001
DOI: 10.1038/sj.bjp.0703860
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and translational regulation of calpain in the rat heart after myocardial infarction – effects of AT1 and AT2 receptor antagonists and ACE inhibitor

Abstract: 1 Recent studies demonstrated that the cardiac calpain system is activated during ischaemic events and is involved in cardiomyocyte injury. The aim of this study was to investigate the contribution of AT 1 and AT 2 receptors in the regulation of calpain-mediated myocardial damage following myocardial infarction (MI). 2 Infarcted animals were treated either with placebo, the ACE inhibitor ramipril (1 mg kg 71 d 71 ), the AT 1 receptor antagonist valsartan (10 mg kg 71 d 71 ) or the AT 2 receptor antagonist PD 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 57 publications
4
27
0
Order By: Relevance
“…Collectively, however, our observations that doxorubicin decreased the expression of calpain-I, induced autolysis of calpain-II to a more proteolytically active form, and that the calpain-II/calpastatin ratio was elevated early relative to calpain-I lead us to speculate that calpain-II may be predominantly responsible for the doxorubicin-induced increase in total calpain activity. This observation is similar to what has been observed early after ischemic cardiac injury, where increases in calpain-II activity, mRNA, and protein levels were much greater compared with those in calpain-I (56,57). Interestingly, a reduction in calpain-I activity and in the rate of calpain-I autolysis has been reported in a neuroblastoma cell line treated with doxorubicin (58).…”
Section: Discussionsupporting
confidence: 73%
“…Collectively, however, our observations that doxorubicin decreased the expression of calpain-I, induced autolysis of calpain-II to a more proteolytically active form, and that the calpain-II/calpastatin ratio was elevated early relative to calpain-I lead us to speculate that calpain-II may be predominantly responsible for the doxorubicin-induced increase in total calpain activity. This observation is similar to what has been observed early after ischemic cardiac injury, where increases in calpain-II activity, mRNA, and protein levels were much greater compared with those in calpain-I (56,57). Interestingly, a reduction in calpain-I activity and in the rate of calpain-I autolysis has been reported in a neuroblastoma cell line treated with doxorubicin (58).…”
Section: Discussionsupporting
confidence: 73%
“…The increase in calpain I activity 14 days post MI was accompanied by a compensated cardiac hypertrophy as evidenced by an increase in THW/BW. Our results are in agreement with ®ndings of previous studies showing a transcriptional and translational up-regulation of calpain I in the non-infarcted hypertrophied rat myocardium (Sandmann et al, 2001). Additionally, studies on rats demonstrated an increase in diastolic myocardial [Ca 2+ ] i in ventricular myocytes of the failing heart which were associated with cardiac hypertrophy following pressure overload (Gwathmey & Morgan, 1985;Steenbergen et al, 1987b) and MI (Sandmann et al, 1999).…”
Section: Calpain I In the Non-infarcted Myocardium Post Misupporting
confidence: 93%
“…The resulting Ca 2+ -overload might activate calpain II which, subsequently, induces myocyte injury and myocardial necrosis. Additionally, in previous experiments, we demonstrated an up-regulation of calpain II in the infarcted region (Sandmann et al, 2001) and Mellgren et al (1988) reported a disappearance of the endogenous calpain inhibitor, calpastatin, in the ischaemic area within the ®rst hours post MI. Thus, it can be speculated that the calpain-calpastatinratio might be shifted to more calpain II in the ischaemic myocardium, leading to abnormal protein degradation and increased myocardial damage following MI.…”
Section: Calpain II In the Infarcted Myocardiummentioning
confidence: 58%
“…Ang II increased the intracellular Ca 2+ , 36 and Ang II may have directly regulated the calpain activity in the brain, as reported in other types of tissues, such as aorta, 37 kidney, 38 and cardiomyocyte. 39 In the present study, the cerebroprotective effects of Ang II vaccine lasted 15 days after the vaccination. Although we could not examine whether the effects were preserved >15 days because of the limitation of the stroke model, the preventive effects of Ang II peptide vaccine may have lasted up to several months because we observed the continuing existence of anti-Ang II antibody in serum at least ≤3 months after immunization.…”
Section: Discussionmentioning
confidence: 94%